Objectively Measured Physical Activity and Body Fatness: Associations with Total Body Fat, Visceral Fat, and Liver Fat - Winters-van Eekelen, Esther (Med Sci Sports Exerc, 2021)
PURPOSE: It remains unclear to what extent habitual physical activity and sedentary time are associated with visceral fat and liver fat. We studied substitution of sedentary time with time spent physically active and total body fat (TBF), visceral adipose tissue (VAT) and hepatic triglyceride content (HTGC) in middle-aged men and women. DESIGN: In this cross-sectional analysis of the Netherlands Epidemiology of Obesity study, physical activity was assessed in 228 participants using a combined accelerometer and heart rate monitor. Total body fat was assessed by the Tanita bio-electrical impedance, VAT by MRI and HTGC by proton-MR spectroscopy. Behavioural intensity distribution was categorized as sedentary time (ST), time spent in light physical activity (LPA), and moderate-to-vigorous physical activity (MVPA). To estimate the effect of replacing 30 minutes/day of ST with 30 minutes/day LPA or MVPA, we performed isotemporal substitution analyses, adjusted for sex, age, ethnicity, education, the Dutch Healthy Diet index, and smoking. RESULTS: Included participants (41% men) had a mean (SD) age of 56 (6) years and spent 88 (56) minutes in MVPA and 9.0 hours (2.1) of ST. Replacing 30 minutes/day of ST with 30 minutes of MVPA was associated with 1.3% less TBF (95% CI: -2.0, -0.7), 7.8 cm(2) less VAT (-11.6, -4.0) and 0.89 times HTGC (0.82, 0.97). Replacement with LPA was not associated with TBF (-0.03 %; -0.5, 0.4), VAT (-1.7 cm(2); -4.4, 0.9) or HTGC (0.98 times; 0.92, 1.04). CONCLUSIONS: Reallocation of time spent sedentary with time spent in MVPA, but not LPA, was associated with less total body fat, and visceral and liver fat. These findings contribute to the development of more specified guidelines on sedentary time and physical activity.